CAR RENTAL SYSTEM AT PT. GKBI INTERNATIONAL TRANSPORT USING MICROSOFT VISUAL BASIC 6.0 - Vify Yanti; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2007)
In this study, the authors try to present information with a computerized rental, so itcan help in performing daily transactions. Existing data on the computer is a tenant ofdata, data, car, rentals, returns and reports.At this time many people need a rental car and the manual recording of data byemployees, then the data is less accurate and efficient. Therefore, the authors providea solution by using a computerized so that data obtained by more accurate andefficient.